THE EFFECT OF STEEL FIBERS ON THE RHYOLOGICAL AND MECHANICAL PROPERTIES OF SELF COMPACTING CONCRETE - Ghanem, Hassan; Obeid, Yehia (European Scientific Journal, ESJ, 2015)
Self-compacting concrete (SCC) is a highly flowable, nonsegregating concrete that has the ability to flow in every spot of the complex formwork and consolidate within that without any external compaction. Steel fiber reinforced self-compacting concrete (SFR-SCC) is a new mixed material that merge the advantages of the SCC with those of steel fibers in improving concrete mechanical properties. This paper is part of a study to analyse the effect of steel fibers on the rheological [J-ring test] and mechanical properties [compressive strength and four point bending test] of SCC. Five concrete mixtures were evaluated. The primary experimental variables are the type and aspect ratio of steel fibers. Test results have shown that the inclusion of fibers improves the compressive strength of SCC but it has a negative effect on the rheological properties of the SCC by reducing the slump flow and increasing the flow time, but better workability was obtained as aspect ratio of the steel fibers decreased. It was also found that the fiber geometry is a key factor affecting the mechanical performance in particular the toughness of the SFR-SCCmaterial.